2022
DOI: 10.3389/fimmu.2022.968336
|View full text |Cite
|
Sign up to set email alerts
|

Protection against influenza-induced Acute Lung Injury (ALI) by enhanced induction of M2a macrophages: possible role of PPARγ/RXR ligands in IL-4-induced M2a macrophage differentiation

Abstract: Many respiratory viruses cause lung damage that may evolve into acute lung injury (ALI), a cytokine storm, acute respiratory distress syndrome, and ultimately, death. Peroxisome proliferator activated receptor gamma (PPARγ), a member of the nuclear hormone receptor (NHR) family of transcription factors, regulates transcription by forming heterodimers with another NHR family member, Retinoid X Receptor (RXR). Each component of the heterodimer binds specific ligands that modify transcriptional capacity of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…the decrease of pulmonary surfactant is the main pathogenesis of VALI (11). Various pathogenic factors inside and outside the lung cause acute uncontrolled inflammatory reactions in lung tissue, resulting in alveolar capillary injury, increased permeability and pulmonary edema, which lead to progressive dyspnea and hypoxemia are the main pathophysiological changes of VALI (12). Alveolar enter the lung tissue, further aggravating the injury of lung tissue and promoting the development of patients with VALI (19).…”
Section: Discussionmentioning
confidence: 99%
“…the decrease of pulmonary surfactant is the main pathogenesis of VALI (11). Various pathogenic factors inside and outside the lung cause acute uncontrolled inflammatory reactions in lung tissue, resulting in alveolar capillary injury, increased permeability and pulmonary edema, which lead to progressive dyspnea and hypoxemia are the main pathophysiological changes of VALI (12). Alveolar enter the lung tissue, further aggravating the injury of lung tissue and promoting the development of patients with VALI (19).…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 or IL-13 can effectively counteract inflammatory damage and promote tissue healing by stimulating macrophages to differentiate into M2a cells and release anti-inflammatory cytokines such as IL-1RA, IL-10, and transforming growth factor-beta (TGF-β) ( 40 , 41 ) via the co-receptor IL-4Rα. Arg1, Mrc1, Chil3, and Retnla are their primary markers of detection ( 42 ). When TLR or IL-1R agonists are exposed to the body, they produce M2b macrophages that release cytokines, IL-10, IL-1, etc., to exert immunomodulatory effects.…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Other viruses, such as RSV, HPIV-3 or H5N1, upregulate COX-2 in bronchial and bronchiolar epithelial cells and macrophages [184][185][186][187]. In a very recent paper, Gopalakrishnan showed that influenza infection induced COX-2 expression in inflammatory macrophages, which contributes significantly to influenza-induced lethality [188]. In contrast, poly(I:C), a viral PAMP that can be considered a synthetic analogue of double-stranded RNA present in, for example, reoviruses, which activates TLR-3, does not enhance COX-2 expression in mouse lung tissue.…”
Section: Cox Pathways In Injured Lung Endotheliummentioning
confidence: 99%